Effect of postharvest on the economic viability of walnut production - Apáti, F.; Kovács, E.; Kocsis, M. (International Journal of Horticultural Science, 2018)
In this study we were studying the question whether walnut production under domestic natural and economic circumstances shall be considered a profitable activity or not. Our partial objective is to determine, what level of natural inputs and production costs are required for walnut production, what yield level, selling price and production value can be attained, what level of profitability, rentability and efficiency may production have, is the establishment of a walnut orchard profitable on the entire lifespan of the plantation, and the production of which is more efficient: the dry shelled walnut production requiring postharvest activity or the raw, shelled walnut without postharvest activities. In this study, comparison of two systems is conducted. First version: producer establishes a walnut plantation and sells walnut raw and shelled. Second version: producer also invests into a drying facility, and in this case the end product is the dry, shelled walnut. If the producer sells walnut right after harvest in a raw bulk, total production costs in productive years reaches 974,011 HUF/ha. Attainable yield is 2.63 t/ha with 396.3 HUF/kg selling price, therefore the profit is 138,258 HUF/ha with 14.19% cost-related profitability. In the case when the producer sells dried, shelled walnut, production costs are 25% higher compared to that of raw walnut due to the cost of drying. By calculating with the postharvest loss, average yield is 1.84 t/ha, however, its selling price is way higher (882.84 HUF/kg), therefore the profit per hectare reaches 475,496 HUF with 39.01% cost-related profitability. Thus it can be stated that walnut production in an average year may be profitable even without postharvest, but efficiency is improved significantly when the producer sells the products dried. Investment profitability analysis revealed that production of raw, shelled walnut is not economically viable, since the plantation does not pay off on its entire lifespan (30 years), while walnut production with postharvest is efficient and rentable, since both net present value (NPV) and internal rate of return (IRR) showed more favourable values than in the previous case, and the orchard pays off in the 21th year after establishment.